Global virtual water trade and the hydrological cycle: patterns, drivers, and socio-environmental impacts - Paolo D’Odorico; Joel Carr; Carole Dalin; Jampel Dell’Angelo; Megan Konar; Francesco Laio; Luca Ridolfi; Lorenzo Rosa; Samir Suweis; Stefania Tamea; Marta Tuninetti (Environmental Research Letters, 2019)
The increasing global demand for farmland products is placing unprecedented pressure on the global agricultural system and its water resources. Many regions of the world, that are affected by a chronic water scarcity relative to their population, strongly depend on the import of agricultural commodities and associated embodied (or virtual ) water. The globalization of water through virtual water trade (VWT) is leading to a displacement of water use and a disconnection between human populations and the water resources they rely on. Despite the recognized importance of these phenomena in reshaping the patterns of water dependence through teleconnections between consumers and producers, their effect on global and regional water resources has just started to be quantified. This review investigates the global spatiotemporal dynamics, drivers, and impacts of VWT through an integrated analysis of surface water, groundwater, and root-zone soil moisture consumption for agricultural production; it evaluates how virtual water flows compare to the major ‘physical water fluxes’ in the Earth System; and provides a new reconceptualization of the hydrologic cycle to account also for the role of water redistribution by the hidden ‘virtual water cycle’.